MANAGERIAL APPROACH OF PRINCIPALS IN ENHANCING THE PERFORMANCE OF TEACHERS AND EDUCATIONAL STAFF AT PUBLIC JUNIOR HIGH SCHOOLS IN BANDA ACEH CITY - Akmaluddin akmal (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
This study aims to describe the leadership management strategies employed by school principals to improve the performance quality of educators and education staff at public junior high schools in Banda Aceh City. The research methodology used in this study is qualitative descriptive, based on observable phenomena, symptoms, and events, and directed towards a holistic understanding of the leadership management strategies of school principals in enhancing the performance quality of educators and education staff. The results of this study indicate that the management strategies implemented by school principals to enhance the performance of educators at public junior high schools in Banda Aceh City include conducting training programs, performance coaching for educators and education staff, organizing Subject Teacher Consultations (MGMP), providing motivation and rewards for outstanding educators, and conducting supervision. The supervision carried out by school principals involves overseeing the work of educators and staff, providing comprehensive teaching facilities and infrastructure, and monitoring the discipline of educators.